2022
DOI: 10.1097/md.0000000000029762
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and validation of potential molecular targets for the combination of Astragalus membranaceus and Angelica sinensis in the treatment of atherosclerosis based on network pharmacology

Abstract: Since the 20 th century, mortality rate due to cardiovascular diseases has increased, posing a substantial economic burden on society. Atherosclerosis is a common cardiovascular disease that requires urgent and careful attention. This study was conducted to predict and validate the potential molecular targets and pathways of Astragalus membranaceus and Angelica sinensis (A&A) in the treatment of atherosclerosis using network pharmacology. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…In particular, the combined application of network pharmacology and modern technologies such as molecular docking can clearly analyze the action targets and regulatory pathways of some complex Chinese medicine prescriptions, and provide directions for further experimental research. [17,18] Utilizing network pharmacology and molecular docking, techniques, this study elucidates the multifaceted mechanisms by which HBCS effectively addresses T2DM through the modulation of multiple targets and pathways. Furthermore, the investigation delves into the identification of key active components, potential targets and pathways associated with the therapeutic efficacy of HBCs in the treatment of T2DM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the combined application of network pharmacology and modern technologies such as molecular docking can clearly analyze the action targets and regulatory pathways of some complex Chinese medicine prescriptions, and provide directions for further experimental research. [17,18] Utilizing network pharmacology and molecular docking, techniques, this study elucidates the multifaceted mechanisms by which HBCS effectively addresses T2DM through the modulation of multiple targets and pathways. Furthermore, the investigation delves into the identification of key active components, potential targets and pathways associated with the therapeutic efficacy of HBCs in the treatment of T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the combined application of network pharmacology and modern technologies such as molecular docking can clearly analyze the action targets and regulatory pathways of some complex Chinese medicine prescriptions, and provide directions for further experimental research. [17,18]…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] Network pharmacology integrates pharmacology, biology, bioinformatics and computer science, and is an ideal method to comprehensively study muti-components and muti-targets as a whole. [21,22] With the aid of database information and network construction of "Medicine-Targetspathways-Disease," network pharmacology can effectively predict the potential mechanisms of Chinese herbs in treating various diseases. [23][24][25] In the present study, we investigated the pharmacological mechanisms of Lycii Fructus against PMOP by using network pharmacology.…”
Section: The Study Was Supported By Natural Science Foundation Of Nin...mentioning
confidence: 99%
“…Network pharmacology is a new discipline aimed at analyzing the biological network systematically based on systems biology, almost all Traditional Chinese Medicine and World Ethnomedicine play a therapeutic role in disease through multiple molecules, it spans traditional and modern medicine, and can reduce the cost of drug development, it is a powerful tool for discovering active substances and revealing the pharmacological mechanisms of Chinese medicines systematically. [13] Combined with network pharmacology techniques, the potential mechanism of some prescriptions of TCM like Fuzheng Yugan Mixture, [14] commonly used Chinese medicine pairs like Astragalus membranaceus and Angelica sinensis, [15] and single components such as luteolin [16] for the treatment of some common diseases have been revealed, providing new ideas for the treatment of diseases. Recently, researchers have conducted a network pharmacology analysis of TCM to uncover the mechanism of TCM on NSCLC, by using network pharmacology techniques, Ye et al [17] revealed the mechanism of Sophora davidii (Franch.)…”
Section: Introductionmentioning
confidence: 99%